Area-based management in polar oceans for biodiversity conservation and enhanced sustainability of fisheries - Misund, Ole Arve; Hop, Haakon; Quillfeldt, Cecilie von (Frontiers in Ocean Sustainability, 2025)
The Polar areas of the Arctic and Antarctic are the coolers of the world. In the Arctic there is floating sea ice covering the more than 4,000 m deep central Arctic Ocean surrounded by islands like Greenland with a thick ice sheet, and Svalbard and other high-Arctic Islands with glaciers. Antarctica is a large continent (about 14.2 mill. km2) with a huge ice sheet, and seasonal sea ice in the surrounding, more than 4,000 m deep, Southern Ocean. The shallow marginal seas like the Barents Sea and the Bering Sea, are influenced by relatively warm, nutrient-rich sea currents, with associated plankton, from lower latitudes and therefore very productive. In the European Arctic there are rich fisheries in salmonids, clupeoids, gadoids, and crustaceans. The circulation of the Southern Ocean is dominated by the strong Antarctic Circumpolar Current, and there is a high abundance of plankton, krill, fish, seabirds, penguins, seals, and whales. The large Antarctic krill resources are subject to a fishery limited to about 600,000 tons annually. Through the working groups PAME and CAFF of the Arctic Council there are ongoing processes for area-based management in Arctic waters. In the territorial waters of the Arctic nations, many examples exist of different categories of Marine Protected Areas (MPA) with different degrees of protection. For the central Arctic Ocean there is an agreement from 2021 of no fishing for the next 15 years until the potential resources in the area has been properly mapped and assessed scientifically. In the Barents Sea, there is a system of temporary real-time closures of large areas for Danish seining and bottom trawling to protect juvenile fishes. The Antarctic Treaty, the Environment Protection Committee, and the Convention of Conservation of Living Marine Resources have been backdrops for ongoing processes to further develop area-based management in the Southern Ocean. Just two marine protected areas are established, but there are several Antarctic Specially Protected Areas (ASPA) and Antarctic Specially Managed Areas (ASMA), both which may have marine components. There are also proposals for several new MPAs. Recently, large areas in the Weddell Sea were discovered to be spawning habitats for icefish (Neopagetopsis ionah). This species lay fertilized eggs in a nest on the bottom substrate, and guard them until hatching. Any kind of active bottom fishing gears or other bottom gears would easily disturb and destroy their habitats. Thus, such areas need protection to conserve vulnerable biodiversity.